Portfolio optimization in high volatile and stable market by using semi-variance and linear programming model / Nor Fariha Mohd Faizail - Mohd Faizail, Nor Fariha (2007)
These studies focus on the portfolio optimization in high volatile and stable market by using semi variance and linear programming model. This model can help the investor in order to minimize his risk of negative return. The main objective of this study is to investigate the efficient market portfolio by using semi variance and linear programming model as alternative to measure risk and return of portfolio. The other objective of this research is to compare the portfolio performance between the highly volatile market and stable market. To analyze the risk and return of semi-variance, this study is using 30 companies from construction sector and 30 companies from consumer sector, which have been listed in Kuala Lumpur Composite Index (KLCI) that has been approved by syariah compliance. 15 companies from consumer sector and 15 companies from construction sector has selected based on high price earning ratio (P/E) and another 15 companies from this two sector are based on lower price earning ratio. The time horizon of this study is from 1997 to 2007 by using monthly data. The finding of this study is in highly volatile market, consumer sector that has high P/E and construction sector that has low P/E in stable market have lower risk of negative return.